P-118 Creating a bridge between communities and hospice services: development of a new way of working to replace traditional day care. (19th November 2022) - Smith, Liz; Malcomson, Mandy; Boa, Sally; Mackay, Marjory; High, Susan
Abstract : Background: Like many hospices throughout the UK (Swann, Easton, McGuinness et al., 2021. BMJ Support Palliat Care. Apr.29), our day service was forced to close due to COVID-19. We have developed a new way of working – 'Live Your Life'. This is developing and evolving with ongoing evaluation. Aim: We aimed to: Put people at the heart of decisions and involvement in their care. Pilot a combination of Goal-Setting and Action-Planning (G-AP PC) (Boa, [PhD thesis], 2014) and Assets Based Community Development (ABCD) (Russell, 2022) alongside palliative support to enable people with life-limiting conditions to live well. Untether the service from our building, and open access, enabling more people to engage with support, including carers. Methods: We designed a model of working between hospice services and communities, in co-production with existing service users. Data collection includes: Referral routes. Outcome measures - Therapy Outcome Measures (TOMs) (Enderby, John & Petheram, 2013) and the Australia - modified Karnofsky Performance Status (AKPS) (Abernethy, Shelby-James, Fazekas, et al., 2005. BMC Palliat Care. 4:1). Anticipatory care planning. Goal achievement. Feedback from people and their families. Results: From 01/08/21- 19/04/22, 88 referrals were received from: Hospice CNS = 78% Other hospice professionals = 4% External professionals = 12% Self-referrals = 6% 15 carers and 88 people received support through a combination of phone, face-to-face and virtual connection, engaging in goal-setting conversations and connection with communities. Results so far show an average increase in participation, wellbeing, performance and anticipatory care planning conversations (before referral 65%, after referral 88%). Conclusion: Initial findings suggest that this way of working enables support for people in the way that suits them best, without them having to come into the building. Self-referral enables a shift in power from professional to person. Hospice services and communities are creating bridges, working together to empower people to drive care to meet their needs. Continued evaluation and data collection will provide further insight into this innovative and new way of working.